Economic Growth and Significant Determinants: An Update - Raza, Fahim (PSM Biological Research, 2022)
Development theories illustrate the progression and economic thought trends that shaped the way economic growth is perceived. Researchers also concentrated on discovering the most significant parameters that affect development by forming new hypotheses and models. We want to propose several variables that strongly influence economic growth and progress. It has not been completely known yet which growing variables have the biggest impact on economic development.